Temporal kinematic and kinetics differences throughout different landing ways following volleyball spike shots - Xu, D.; Lu, J.; Baker, J. S.; Fekete, G.; Gu, Y. (Proceedings of the Institution of Mechanical Engineers, Part P: Journal of Sports Engineering and Technology, 2022)
Volleyball players often land on a single leg following a spike shot because of a shift in the center of gravity. This landing is one of the high-risk actions for non-contact ACL injury. The purpose of this study was to compare and analyze the discrete and temporal kinematics and kinetics associated with functional valgus collapse during volleyball in player landing phases during a single-leg landing and double-leg landing following a spike shot. Kinematics and kinetics data were collected (captured by a Vicon motion system and AMTI force plate, processed by Visual-3D software) during the single-leg and double-leg landing phases in 13 semi-professional male volleyball players. The landing phase was defined as initial ground contact (0% landing phase) to maximum knee flexion (100% landing phase). Statistical Parametric Mapping (SPM) analysis revealed that single-leg landing depicted a significantly greater knee abduction angle and hip adduction moment than double-leg landing during the 0%-68% landing phase (single-leg: 7°-16°, double-leg: 0°-9°, p < 0.001) and 18%-22% (single-leg: 0.62-0.91 Nm/kg, double-leg: 0.08-0.19 Nm/kg, p = 0.0063) landing phase, respectively. The traditional discrete analysis revealed that single-leg landing depicted a significantly greater peak knee internal rotation moment (single-leg: 1.46 ± 0.38 Nm/kg, double-leg: 0.79 ± 0.19 Nm/kg, p = 0.006) and peak hip internal rotation moment (single-leg: -2.20 ± 0.54 Nm/kg, double-leg: -0.88 ± 0.30 Nm/kg, p = 0.011) than double-leg landing. Most differences were within a time frame during the landing phase of 30-50 ms in which non-contact ACL injuries are considered to happen. These recorded time frames are consistent with biomechanical measures that are deemed dangerous. To reduce lower limb injury, a volleyball player should consciously swing the arms to influence the body to maintain a better-balanced state. Adjusting the landing mode of the lower limbs can achieve a good cushioning effect during landing following a spike shot.